Estrutura produtiva, desigualdade regional e distribuição de renda : dois ensaios para o estado da Bahia - Silva, Libania Araújo (2018)
The present study consists of two independent essays that approach two types of inequality on the state of Bahia which, although being related, have distinct features. The first essay sought to understand the dynamics of production and income disparities between the micro regions of the state of Bahia and to decompose the regional employment growth between 2004-2014, using the Williamson’s coefficient and the shift-share analysis. The results showed that there was a reduction of the interregional inequality of income in the Brazilian territory of Bahia, as well as the reallocation of the formal employment by the productive activities in the micro regions. On the other hand, the second essay brings a discussion about the productive structure influence on the changes in the interpersonal income distribution in the Brazilian State of Bahia. In this case, the base of the analysis is the application of Leontief-Miyazawa’s (1976) model and the impact measurement of exogenous changes on the income. For this purpose, we used data from an input-output matrix of the Bahia state for the year 2009 (PEROBELLI et al., 2015), as well as information about families consumption and income from Household Budge Survey – POF 2002/2003 – and the National Household Sampling Survey – PNAD 2009. Following, we run two simulations aiming to analyze the income’s transfer impact, respectively, on poor and extremely poor families, and the measurement of the Gini's coefficients. The results suggest that the productive sectors present different capacities among themselves to cause changes upon the income distribution, and that governmental transfer cause the reduction of income inequality in the Brazilian State of Bahia.